The psychology of extremism a motivational perspective - Kopetz, Catalina E.; Kruglanski, Arie W.; Szumowska, Ewa 1986- (Frontiers of social psychology, 2022)
"This ground-breaking book introduces a new model of extremism that emphasizes motivational imbalance among individual needs, offering a unique multidisciplinary exploration of extreme behaviors relating to terrorism, dieting, sports, love, addictions, and money. In popular discourse, the term 'extremism' has come to mean largely 'violent extremism', but this is just one of many different types: extreme sports, extreme diets, political and religious extremisms, extreme self-interest, extreme attitudes, extreme devotion to a cause, addiction to substances, or behavioral addiction (to videogames, shopping, pornography, sex, work). But do these descriptions have a deeper meaning? Do they reveal a common psychological dynamic? Or are they merely a mode of things about phenomena that have little in common? Bringing together world-leading psychologists from a variety of disciplines, the book uses a brand-new model to examine different expressions of extremism, at different levels of analysis (brain, hormones, behavior), in order to not merely to describe such behaviors but also to explain their occurrence, and the conditions under which they may be likely to emerge. Also including suggestions for ways in which extremism could be counteracted, and to what extent it appears to be harmful to individuals and society, this is essential reading for students and academics in psychology and behavioral sciences"-- Provided by publisher.